Key performance indicators of the academic advising system and student performance among Saudi undergraduate dental students: a retrospective analysis - Baghlaf, Khlood; Al-Attas, Safia (Frontiers in Education, 2025)
BackgroundAcademic advising should be central to an institution’s educational mission, rather than merely treated as an additional service.AimsThis study evaluates the effectiveness of the academic advising (AA) system at the Faculty of Dentistry over 5 years, emphasizing its essential role in fostering student success and achievement. It investigates the connection between academic advising meetings and student performance as indicated by grade point average (GPA). In addition, this study provides ratings for academic advising systems.MethodsA retrospective cross-sectional analysis was conducted by collecting data from undergraduate students regarding their participation in AA meetings and their academic performance over the past 5 years. Key performance indicators were calculated from 2021–2025. The analysis of data from 2024 examined the mean GPA and its association with the number of AA sessions attended.ResultsA significant increase was observed in key performance indicators from 48.31% in 2021 to 68.50% in 2025, reflecting enhanced student engagement and advising effectiveness. Furthermore, a positive correlation was identified between the frequency of advising meetings and student GPA, with high achievers participating in more meetings than lower-achieving peers. Female and senior students demonstrated greater advising engagement and academic success. The study also highlights the challenges faced by the academic guidance unit, such as faculty time limitations and uncooperative student behavior, which impede effective advising.ConclusionThis study presents recommendations for improving the AA process, stressing the importance of ongoing evaluation and adopting innovative strategies to better address student needs. Overall, the results highlighted the vital role of academic advising as a foundational aspect of the educational experience that facilitates personal growth and academic success among students.